Nature is Local Wisdom Treasures in Indonesia Ecotourism - Miya Dewi Suprihandari; Muhammad Ali Masyhuri; Teguh Purnomo; Menur Kusumaningtyas; Nurul Iman; Muhammad Aly Umar (Journal of Islamic Economics Perspectives, 2021)
Kampung and tourism villages in Indonesia are a positive phenomenon that can function as an effort to increase the income of the village or village community directly and indirectly for local and central government. Efforts to present the local wealth of the region as an added value of an area, so that the growth rate of tourist visits in an area in Indonesia is increasing from the past. The number of village and tourist village destinations in Indonesia has also increased from the past and entrepreneurial activities have become an option for most members of village and tourism village communities in various forms. Efforts to explore and develop local capabilities and wealth will provide optimal results when the government provides full support for the capabilities and creativity of local communities in all matters, including training for community members who are interested and have a desire to increase knowledge and increase their creative abilities, so that they can become human resources who are able to compete in the future and have character. This support is carried out continuously because villages and tourist villages in Indonesia currently also have an educational function for all ages and levels of education.